INTEGRASI KEUANGAN MIKRO ISLAMIC UNTUK KESEJAHTERAAN MASYARAKAT - Hamdani, Hamdani (Commodity : Jurnal Perbankan dan Keuangan Islam, 2024)
The study of the integration of Islamic microfinance in improving community welfare aims to investigate the role of Baitul Maal Wattamwil (BMT) finance in contributing to the economic progress of the community, especially for Al-Quran teachers. BMT has two functions, namely financing the economy and distributing zakat and infaq funds. In fact, the existence of BMT is in great demand by the community, especially among Al-Quran teachers, mosque activists and Islamic study groups. The reason is, BMT provides convenience in financing the family economy, while for Al-Quran educational institutions, they still receive social assistance through Islamic social finance, infaq and alms